2016
DOI: 10.1080/23120053.2016.1216816
|View full text |Cite
|
Sign up to set email alerts
|

Pathological vestibular symptoms presenting in a group of adults with HIV/AIDS in Johannesburg, South Africa

Abstract: The current study aimed to explore the pathological vestibular symptoms presenting in a group of adults with HIV/AIDS in Johannesburg, South Africa. Design: A quantitative non-experimental research design was adopted where data was collected by means of a questionnaire with close-ended questions on 96 participants who were recruited from a teaching hospital's HIV/AIDS research unit. Analysis: Data were analysed through descriptive statistics. Results: Findings from the current study revealed that 17% of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It was concerning that almost half the participants (47%) indicated that they would only sometimes wear gloves during evoked potentials and vestibular testing; however, it was encouraging that an equal number indicated that they would always wear gloves. It was important to note that about a quarter of the participants from Khoza-Shangase and Van Rie’s study (2017) reported that they had diminished hearing sensitivity since being diagnosed with HIV and AIDS. This is further supported by the literature from Heinze, Swanepoel and Hofmeyer (2011), in which reports of auditory and vestibular manifestations were identified in patients with HIV and AIDS (Heinze et al, 2011), necessitating audiological services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concerning that almost half the participants (47%) indicated that they would only sometimes wear gloves during evoked potentials and vestibular testing; however, it was encouraging that an equal number indicated that they would always wear gloves. It was important to note that about a quarter of the participants from Khoza-Shangase and Van Rie’s study (2017) reported that they had diminished hearing sensitivity since being diagnosed with HIV and AIDS. This is further supported by the literature from Heinze, Swanepoel and Hofmeyer (2011), in which reports of auditory and vestibular manifestations were identified in patients with HIV and AIDS (Heinze et al, 2011), necessitating audiological services.…”
Section: Discussionmentioning
confidence: 99%
“…Its treatment includes a group of antibiotics termed aminoglycosides, which are ototoxic and target the cochlea vestibular system. Managing individuals with TB requires the inclusion of the appropriate HCPs, including audiologists, who are essential in monitoring the effects of ototoxic medication on hearing (Khoza-Shangase, 2013). A South African study by Khoza-Shangase and Van Rie (2017) conducted with 96 participants from an HIV and AIDS research unit indicated that, of those diagnosed with HIV and AIDS, 14% reported co-occurring vestibular symptoms and 69% reported experiencing co-occurring audiological symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing health care in developing countries are numerous. South Africa has the largest number of people living with HIV/AIDS [7]. Disorders of the auditory and vestibular system, including otitis media, are often associated with HIV/AIDS [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa has the largest number of people living with HIV/AIDS [7]. Disorders of the auditory and vestibular system, including otitis media, are often associated with HIV/AIDS [7, 8]. Otitis media as a global middle ear disease is reported to be as high as 11% in some African countries, with severe economic implications [9].…”
Section: Introductionmentioning
confidence: 99%